13th Applied Aerodynamics Conference 1995
DOI: 10.2514/6.1995-1881
|View full text |Cite
|
Sign up to set email alerts
|

Gurney flap effects and scaling for low-speed airfoils

Abstract: The effects of Gurney flaps were tested on two airfoil sections, the LA203A and the Gottingen 797, in a low speed wind tunnel. Lift and drag forces, wall-pressure distributions and boundarylayer thickness measurements have been carried out,. Different Gurney flap heights ranging from 0.5% to 5.0% chord have been tested in order to identify some optimal configuration of this simple, yet promising device. The results presented are for a chord Reynolds number of 250 000 and reveal, in accordance with higher Reyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 6 publications
2
42
0
2
Order By: Relevance
“…Additionally, the light reductions of drag coefficient relative to the clean blade-encountered with both pressure and SS actuation-are in agreement with other results found in literature on trailing edge devices (see e.g., Refs. [16][17][18][19][20]49]). It is also worth remarking that the present fully-turbulent RANS assessments can't provide a quantitative evaluation of drag.…”
Section: Results At Constant Angle Of Attackmentioning
confidence: 99%
“…Additionally, the light reductions of drag coefficient relative to the clean blade-encountered with both pressure and SS actuation-are in agreement with other results found in literature on trailing edge devices (see e.g., Refs. [16][17][18][19][20]49]). It is also worth remarking that the present fully-turbulent RANS assessments can't provide a quantitative evaluation of drag.…”
Section: Results At Constant Angle Of Attackmentioning
confidence: 99%
“…Surface pressure measurements [16,17,20] have shown that the increase in lift coefficient was caused by the Gurney flap increasing both the peak suction and the trailing edge loading. Moving the Gurney flaps forward from the trailing edge did not eliminate this effect [17].…”
Section: The Gurney Flapmentioning
confidence: 99%
“…Giguére et al [6], described experimentally the aerodynamic behavior of these flaps scaling their height with the boundary layer thickness.…”
Section: Introductionmentioning
confidence: 99%